2002
DOI: 10.1002/dvdy.10151
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of N‐cadherin function in limb mesenchymal chondrogenesis in vitro

Abstract: During embryonic limb development, cartilage formation is presaged by a crucial mesenchymal cell condensation phase. N-Cadherin, a Ca 2؉ -dependent cell-cell adhesion molecule, is expressed in embryonic chick limb buds in a spatiotemporal pattern suggestive of its involvement during cellular condensation; functional blocking of N-cadherin homotypic binding, by using a neutralizing monoclonal antibody, results in perturbed chondrogenesis in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
112
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(120 citation statements)
references
References 56 publications
5
112
1
1
Order By: Relevance
“…The formation of cellular condensations precedes the commitment of mesenchymal cells to the chondrogenic lineage (6,7). Inhibition of Rac1 signaling resulted in decreased mesenchymal condensation, as confirmed by decreased PNA staining and reduced expression of N-cadherin.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of cellular condensations precedes the commitment of mesenchymal cells to the chondrogenic lineage (6,7). Inhibition of Rac1 signaling resulted in decreased mesenchymal condensation, as confirmed by decreased PNA staining and reduced expression of N-cadherin.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the expression of the deletion mutant form of N-cadherin, which lacks either the extracellular homotypic interaction domains or the intracellular β-catenin binding site, results in decreased cellular condensation and impaired chondrogenesis (21,22). These findings suggest that both extracellular homotypic interaction and intracellular interaction with the catenin complex are essential for proper N-cadherin signaling (23).…”
mentioning
confidence: 99%
“…Mesenchymal condensation is a prerequisite for chondrogenesis and is facilitated by cell adhesion molecules. Upregulation of cell adhesion proteins such as N-cadherin is a hallmark of condensing cells, whereas loss of cell adhesion molecules is able to abolish condensation (Delise and Tuan 2002;Bobick et al 2009). The molecular mechanisms governing condensation are not fully understood, though several genes have been implicated in this process such as bone morphogenic proteins (BMPs) and SRY (sex determining region Y)-box 9 (Sox9) (Fromental-Ramain et al 1996;Wada et al 1998;Lu et al 2008).…”
mentioning
confidence: 99%